The Effect Of Physical Facilities, Location Strategy, And Product Innovation On Culinary Tourist Satisfaction : Case Study of Mie Gacoan Consumers In Bogor City - Muhammad Arya Ghifari; Sujana Sujana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to 1) To determine the effect of physical facilities on customer satisfaction of Gacoan Noodles in Bogor City. 2) To determine the effect of Location Strategicity on customer satisfaction of Mie Gacoan in Bogor City. 3) To determine the effect of product innovation on customer satisfaction of Mie Gacoan Bogor City. Physical facilities are equipment provided by the company to support the activities carried out by consumers. A strategic location or close to schools, offices, universities can make it easier for consumers to come to the location of a business. Product innovation is the development of a product while maintaining product quality. Customer satisfaction is the feeling that arises after comparing it with their expectations. Data collection was collected as many as 220 respondents. Data processing Analysis of Moment Structure (AMOS) with the Structural Equation Modeling (SEM) analysis method. The results of this study are Physical Facilities have no significant effect on Customer Satisfaction, Location has a significant effect on Customer Satisfaction, Product innovation has no significant effect on Customer Satisfaction. The physical facilities provided are not good enough, the Location Strategicity is good enough for consumers, and product innovation is not good enough. Keywords: Physical Facilities, Location Strategicity , Product Innovation, Consumer Satisfaction